Overexpression of NIMA related kinase 2 in multiple myeloma and its relevance with disease features and prognosis to bortezomib treatment. (10th September 2022) - Gu, Xiaolin; Wang, Zhenhua; Pan, Qiqun
Abstract: What is Known and Objective: NIMA related kinase 2 (NEK2) promotes the malignant transformation and enhances the chemoresistance to proteasome inhibitor in multiple myeloma (MM) cell lines. The current study aimed to further investigate its correlation with clinical features and responsiveness to bortezomib treatment in MM patients. Methods: Totally, 76 MM patients and 30 health donors (HDs) were enrolled to collect bone marrow plasma cells for NEK2 detection using reverse transcription quantitative polymerase chain reaction (RT‐qPCR). Meanwhile, NEK2 siRNA was transfected into the RPMI‐8226 and KMS‐11 cells, subsequently their cell viability was evaluated using Cell Counting Kit‐8 reagent after treatment with different doses of bortezomib. Results and Discussion: NEK2 expression was higher in MM patients compared with HDs ( Z  = −5.123, p  < 0.001). Besides, elevated NEK2 expression was associated with the occurrence of the bone lesion ( χ 2  = 4.610, p  = 0.032) and t (4; 14) ( χ 2  = 3.971, p  = 0.046). Additionally, elevated NEK2 expression was correlated with declined objective response rate (ORR) ( χ 2  = 4.808, p  = 0.028), but not with complete response (CR) ( χ 2  = 2.341, p  = 0.126). More importantly, elevated NEK2 expression was correlated with shorter progression‐free survival (PFS) ( χ 2  = 8.352, p  = 0.039), but not with overall survival (OS) ( χ 2  = 5.624, p  = 0.131), What is more, NEK2 silence decreased the cell viability under bortezomib treatment and the inhibitory concentration (IC50 ) value of bortezomib in RPMI‐8226 and KMS‐11 cell lines (all p  < 0.05). What is New and Conclusion: NEK2 overexpression links with occurrence of bone lesion, t (4; 14), and poor prognosis to bortezomib treatment in MM patients. Abstract : A total of 76 multiple myeloma (MM) patients and 30 health donors (HDs) were enrolled to collect bone marrow plasma cells for NIMA related kinase 2 (NEK2) detection using RT‐qPCR. Meanwhile, NEK2 siRNA was transfected into the RPMI‐8226 and KMS‐11 cells (MM cell lines), subsequently their cell viability was evaluated using CCK8 reagent. NEK2 expression was higher in MM patients compared with HDs. Besides, elevated NEK2 expression associated with the occurrence of the bone lesion and t (4; 14). Additionally, elevated NEK2 expression correlated with declined objective response rate (ORR) and shorter progression‐free survival (PFS). What is more, NEK2 silence decreased the cell viability under bortezomib treatment and the IC50 value of bortezomib in RPMI‐8226 and KMS‐11 cells (MM cell lines).